Tingkat Pendidikan Sebagai Penentu Takaran Belis pada Gadis Sumba - Syahrul Syahrul; Amirulah Datuk; Elisabeth Bora (LPPM IAIN Parepare, 2020)
This research aims to describe the impact of education on Sumba Women in marriage culture. The approach which is used in this research is descriptive qualitative. The subject of this research is Sumba community in NTT Province. The data was collected by interview, observation, and filed notes. This data analyzed by the Miles and Hubermann technique which is obtained from the fact situation in the field, reduction data, display data, verification data, description data, and conclusion. The result of the research showed that the process of marriage tradition of Sumba people, especially women in Sumba Regency were already the changing the dowry (belis) which was determined according to the level of women education, and not based on the social strata or her mother dowry before. The marriage tradition process of Sumba people is no longer maintained traditionally, but they follow the times or modern era.